Critical Discourse Analysis Of Newspaper Article "Courtroom Quarrel Marks Student Protesters Trial" - Muhammad Sukirlan (LINGUISTIKA, 2010)
This research is intended to (I) to observe the process types used in this articles, (2) to investigate the circumstances typed described in this article, (3) to know the participants involved in the text and (4) to disclose the relationship between the text and the social context. in order to answer the aforementioned questions, the writer uses a descriptive qualitative (naturalistic) design, and the data of this study were taken from the samples of newspaper article entitled "Courtroom Quarrel Marks Student Protesters Trial" written in The Jakarta Post, Thursday, October 16, 2008). The text is analyzed using Functional Grammar Analysis (by analyzing the theme and rheme and the transitivity elements). The results indicated that the text is dominantly numbered by the material process explaining that doing words are very dominant, whereas, the types of participants involved are ranged from specific legal context such as lawyer, defendant, witness, the court, the trials, the officials, etc. The writer of the text seems to show that in Indonesia, the power relation between the new order era and the reformed era has changed in a number of aspects.